Differences in HIV, Syphilis, and Hepatitis B Virus Screening Coverage between Pregnant Women Presenting to Antenatal Care in Early and Late Pregnancy in Indonesia - Fatiah, Mona Safitri; Laksono, Agung Dwi; Irjayanti, Apriyana; Syarif, Afwan (Malaysian Journal of Medical Sciences, 2025)
Background: Timely initiation of antenatal care (ANC), defined as the first ANC visit during the first trimester, is critical for the elimination of mother-to-child transmission (EMTCT) of human immunodeficiency virus (HIV), syphilis, and hepatitis B virus (HBV). In Indonesia, service coverage for these infections remains uneven, and the sociodemographic and service-related determinants of complete screening are not well understood.Methods: We analysed data from the 2023 Indonesian Health Survey in a cross-sectional study of pregnant women. Multivariable logistic regression was used to assess the effects of ANC initiation timing, maternal education, parity, and region on complete screening coverage, defined as receipt of all three recommended for HIV, syphilis, and HBV.Results: Most respondents were aged 20 to 34 years, and over half initiated ANC in the first trimester. Screening coverage exceeded 75% in Java, Nusa Tenggara, Kalimantan, and Papua, but was below 45% in parts of Sumatra and Eastern Indonesia. Late ANC initiation was associated with lower odds of complete screening (adjusted odds ratio [AOR]) = 0.68; 95% CI: 0.53, 0.86; P < 0.05). Regional disparities persisted after adjustment: women in Sumatra (AOR = 0.32; 95% CI: 0.25, 0.42), Sulawesi (AOR = 0.59; 95% CI: 0.45, 0.79), and Maluku-Papua (AOR = 0.47; 95% CI: 0.33, 0.69) had significantly lower uptake compared with Java-Bali. Lower educational attainment and high parity were also associated with reduced screening.Conclusion: Timing ANC initiation, maternal education, parity, and region of residence are strong determinants of comprehensive screening coverage for HIV, syphilis, and HBV among pregnant women. Policy efforts should focus on promoting early ANC attendance and reducing regional inequities to accelerate EMTCT progress in Indonesia.